(untitled) - Bargiela-Chiappini, Francesca; Gotti, Maurizio (Bern, 2005)
Includes bibliographical references
Keywords: Business communication -- Asia; Giao tiếp kinh doanh -- Châu Á; Diễn đàn kinh doanh -- Châu Á